2021
DOI: 10.1007/s13320-020-0612-3
|View full text |Cite
|
Sign up to set email alerts
|

A Probe-Shaped Sensor With FBG and Fiber-Tip Bubble for Pressure and Temperature Sensing

Abstract: A probe-shaped sensor for simultaneous temperature and pressure measurement was reported in this article. The effective length of the sensor was ∼2mm, consisting of a fiber Bragg grating (FBG) and a Fabry-Perot interferometer (FPI) with a nano silica diaphragm. The response sensitivities of the sensor for pressure and temperature were measured as −0.98 nm/MPa and 11.10 pm/°C, respectively. This sensor had an extremely low cross-sensitivity between pressure and temperature, which provided a significant potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Since the former is not sensitive to pressure, it can eliminate the temperature crosstalk generated by the F‐P cavity through its temperature response, realizing dual sensing of temperature and pressure. [ 203 ] The team further improved the structure in 2023 to achieve highly sensitive crosstalk‐free sensing of temperature and humidity using the same principle, as shown in Figure a. [ 49 ] In addition, due to the high‐quality factor of the whispering gallery mode(WGM) cavity, the disturbance of the external environment will significantly change the position of its spectral lines, and temperature sensing can also be realized through the frequency shift of the WGM cavity.…”
Section: Applicationmentioning
confidence: 99%
“…Since the former is not sensitive to pressure, it can eliminate the temperature crosstalk generated by the F‐P cavity through its temperature response, realizing dual sensing of temperature and pressure. [ 203 ] The team further improved the structure in 2023 to achieve highly sensitive crosstalk‐free sensing of temperature and humidity using the same principle, as shown in Figure a. [ 49 ] In addition, due to the high‐quality factor of the whispering gallery mode(WGM) cavity, the disturbance of the external environment will significantly change the position of its spectral lines, and temperature sensing can also be realized through the frequency shift of the WGM cavity.…”
Section: Applicationmentioning
confidence: 99%
“…In 2019, Noor et al [ 10 ] reported that the sensitivity of a temperature sensor using multimode interference generated by a single mode-multimode-single mode fiber was approximately 21 pm/°C; Han et al [ 11 ] reported a CLC film, based on a side polished fiber environmental temperature sensor with a sensitivity of ~1.7 nm/°C and a measurable temperature range of 20–50 °C. In 2021, Liu et al [ 12 ] reported a temperature and pressure sensor based on FBG and fiber-tip bubble, with a sensitivity of 11.1 pm/°C and a measurable temperature range of 20–100 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Sensors are key ingredients of next-generation electronics in the Internet of Things (IoT) because they contribute to collecting essential signals. The development of various sensors, including photosensors [1][2][3][4], gas sensors [5,6], temperature sensors [7][8][9], and biosensors [10][11][12][13] is extensive, which accelerates innovation in new technologies such as the aforementioned IoT. To realize the desired sensing functions, detection performance, such as high sensitivity, robust immunity to noise, and fast response times, should be comprehensively improved [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%